Language for Specific Purposes: using Hispanic films and current Hispanic issues to teach specific vocabulary and context related to the professions online - Espino-Bravo, Chita (2023)
In this study I explain how an advanced Spanish conversation course can be created for virtual students using Spanish for Specific Purposes. The course is divided in different online homework students need to work on using four Hispanic films. This course is taught online and asynchronously. Students need to watch four films in this course, work on quizzes about the films, work on debates, and group presentations that are uploaded on VT (Voice Thread). The most important aspect of creating an advanced Spanish conversation course online is to define the goals and outcomes of the course very well and find the films that best serve to teach Spanish language and vocabulary related to the professions. Most films had a main topic, but there were other themes as well in the films students could learn about and use as interesting topics for their presentations in Spanish.